Pengaruh Viral Marketing dan Kualitas Produk Terhadap Keputusan Pembelian Produk Somethinc di Kota Surakarta Dimediasi oleh Citra Merek - Nasla Bintang Pramudita; Edy Purwo Saputro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the impact of viral marketing, product quality, and brand perception on the purchasing decision of Somethinc products in the Surakarta area. The research adopts a quantitative approach using a survey method, with data collected through questionnaire distribution. The study sample consists of 102 participants selected using the purposive sampling technique. The findings indicate that viral marketing and product quality have a positive and significant influence on purchasing decisions, both directly and indirectly through brand perception as a mediating variable. Additionally, brand perception also positively affects purchasing decisions. This study contributes to a deeper understanding of the influence of marketing elements in enhancing the purchasing decisions of domestic products.